WAYS TO INCREASE THE EXPORT CAPACITY OF TEXTILE INDUSTRY ENTERPRISES - Muxtarov Maxmudjon Marifovich (Journals Park Publishing, 2025)
This article provides a comprehensive analysis of the issues of increasing the export potential of textile industry enterprises. In the current global economic climate, the development of new export markets for the textile industry of Uzbekistan, bringing product quality to international standards, and producing finished products with high added value are of urgent importance. The author considers the existing problems in the industry, their causes, and ways to eliminate them. In particular, practical proposals are put forward on the development of export infrastructure, improving the logistics system, increasing competitiveness in foreign markets, and mechanisms for state support for enterprises producing export-oriented products.
Keywords: Textile industry, export potential, foreign markets, finished products, international standards, logistics system, investment, competitiveness, export strategy, added value, economy of Uzbekistan.